Transparency and International Investor Behavior - Wei, Shang-Jin (IMF Working Papers; Working Paper ;, 2002)
Does country "transparency" affect international portfolio investment? We examine this and related questions using a unique micro dataset on international portfolio holdings. We employ various indices of government and corporate transparency, focusing on the availability and quality of information. We find that emerging market equity funds hold fewer assets in less transparent countries. Herding among funds is somewhat less prevalent in more transparent countries. During the Asian and Russian crises, emerging market funds withdrew more strongly from less transparent countries after controlling for other risk factors. However, funds tend to react less strongly to news from more opaque markets.